PENGARUH LOCUS OF CONTROL, BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN STRUKTUR AUDIT TERHADAP KINERJA AUDITOR - Dinda Ilmatiara; Mulia Sosiady; Desrir Miftah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
Public trust in auditors or audit firm as an independent party authorized to audit financial statements is very high. Auditors who can improve their performance are believed to be capable of becoming qualified auditors and capable of producing high quality products. This study aims to analyze the effect of locus of control, organizational culture, organizational commitment, and audit structure on auditor performance. The population in this study were all auditors at the level of partners, managers, seniors, and juniors as well as staff auditors at the Public Accounting Firm in Pekanbaru. The sampling technique used purposive sampling. The technique of collecting data using a questionnaire. This study was tested with multiple regression analysis using the SPSS 23 program. The results showed that locus of control, organizational culture, organizational commitment, and audit structure had an effect on auditor performance.